Efficiency Increase at Low Temperatures through Heat Accumulation Tube Sections in Synthetic Material Damp-Proof Luminaires with T5 Fluorescent Lamps - Pracht, F. (Elektronika ir Elektrotechnika, 2011)
The new energy-saving fluorescent lamp generation T5/16 mm exhibits an extremely high operational efficiency at room tempera-ture. However, low ambient temperatures cause a significantly reduced luminous flux and thus a low operational efficiency. It is there-fore for economic reasons not practical to deploy this new generation of lamps at low temperatures. In the present paper and engineering solution is discussed which is capable of improving the luminous flux in consideration of the special conditions in higher protection class luminaries. Ill. 2, bibl. 8 (in English; abstracts in English and Lithuanian). http://dx.doi.org/10.5755/j01.eee.110.4.307